Practical seismic design procedure for steel braced frames with segmental elastic spines. (February 2019) - Chen, L.; Tremblay, R.; Tirca, L.
Abstract: A practical seismic design method is proposed for tall steel braced frames with segmental elastic trussed spines (SESBFs) used to achieve a uniform storey drift response. The method combines the forces arising from yielding of ductile elements along the braced frame height with the forces resulting from higher modes involving flexural dynamic response of the elastic truss segments. The first set of forces is obtained from static analysis whereas response spectrum analysis is used for the second one. The method is applied and validated for 8-storey and 16-storey SESBFs derived from conventional EBFs. The SESBF configurations including one, two, and four elastic truss segments were examined. The studied structures were located in Vancouver, B.C., and their behaviour was examined through nonlinear time history analysis. The proposed design method provides excellent predictions of the peak force demand imposed on the truss members. The elastic flexural response of truss segments is not bounded by yielding of the frame ductile elements and was found to be sensitive to ground motion signatures and damping assumptions. For taller frames with long truss segments, complete yielding of an individual segment as assumed in design was not observed in the analyses and the proposed method predicted conservative member forces. Highlights: A practical design method for SESBFs is developed and validated numerically The method uses modal superposition technique and response spectrum analysis The method can accurately predict maximum forces in structural members SESBFs designed with the method exhibit good seismic response